Decreased levels of H3K9ac and H3K27ac in the promotor region of ovarian P450 aromatase mediated low estradiol synthesis in female offspring rats induced by prenatal nicotine exposure as well as in human granulosa cells after nicotine treatment. (June 2019) - Fan, Guanlan; Zhang, Qi; Wan, Yang; Lv, Feng; Chen, Yunxi; Ni, Yuan; Zou, Wen; Zhang, Wei; Wang, Hui
Abstract: Prenatal nicotine exposure (PNE) could induce ovarian dysplasia in offspring. This study aimed to confirm its intrauterine origin and explore a programming mechanism of ovarian dysplasia caused by PNE. Pregnant Wistar rats were injected subcutaneously with nicotine (2 mg/kg.d) from gestation day (GD) 9 to GD20. Serum of female offspring was obtained for hormone assays and ovarian tissues were collected. The results showed that PNE impaired ovarian development, and inhibited estradiol production and cytochrome P450 aromatase (P450arom) expression before and after birth. Moreover, the nicotinic acetylcholine receptors (nAChRs) expression was increased in utero, while histone 3 lysine 9 acetylation (H3K9ac) and H3K27ac levels in the P450arom promoter region were decreased persistently in PNE group before and after birth. In vitro, nicotine decreased P450arom expression and estradiol production in human granulosa cell line KGN. Furthermore, nicotine treatment up-regulated nAChRα6 and α9 expression and down-regulated the H3K9ac and H3K27ac levels of the P450arom promoter region. Non-specific nAChRs inhibitor vecuronium bromide reversed these effects. These results suggest that PNE could induce ovarian dysplasia and inhibit estradiol synthesis in the female offspring rats, which was related to the decreased H3K9ac and H3K27ac levels in the promotor region of the P450arom via the nAChRs. Highlights: Prenatal nicotine exposure (PNE) resulted in ovarian dysplasia before and after birth. Nicotine-induced low P450arom expression via nAChRs contributed to a reduced ovarian estradiol synthesis. Decreased H3K9ac and H3K27ac levels within the promotor region of P450 aromatase mediated the reduced estradiol production.